Severity of Liver Injury and Its Relation to Clinical Outcome and Duration of Hospitalization in COVID 19 Patients - Kumbara, Cokorde Istri Yuliandari Krisnawardani; Mariadi, I Ketut; Somayana, Gde; Wibawa, I Dewa Nyoman; Sindhughosa, Dwijo Anargha (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Background: Coronavirus Disease 2019 (COVID-19) can affect not only the respiratory system but also other organs such as the liver. Liver injury tends to occur in severe disease of COVID-19 patients and might contribute to clinical outcomes for patients. This study aimed to find the relationship between the severity of liver injury with clinical outcome and duration of hospitalizations.Methods: This study was a retrospective study of hospitalized COVID-19 patients period April 2020 to April 2021. The inclusion criteria were severe COVID-19 patients who developed a liver injury. The severity of the liver injury was classified into mild, moderate, and severe. The relationship between the severity of liver injury with clinical outcome and duration of hospitalization was analyzed. Univariate and logistic regression were used. Results: 90 samples fill the inclusion criteria. The liver injury severity was statistically significantly related to clinical outcome patients (p= 0.047), which is the increase in liver injury severity resulting in poor clinical outcomes. No significant relationship was found between the severity of liver injury with the duration of hospitalization.Conclusion: liver injury increases mortality in severe COVID-19 patients.